Efectos del entrenamiento de fuerza en la velocidad de golpeo en tenistas jóvenes - Terraza-Rebollo, M.; Baiget, E.; Corbi, F.; Planas Anzano, A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
Nowadays, hitting speed is an important component of tennis performance. The purpose of this study was to determine the effect of two different strength training methods on hitting speed. 20 tennis players were (mean ± SD: age 15.5 ± 0.9 years; weight 61.4 ± 7.6 kg; height 170.3 ± 9.4 cm) randomly divided into 3 groups. During 8 weeks with a frequency of 3 days per week, the first group (SC) performed one additional training with overloads, the second group (L) completed an additional training with medicine ball and elastic band; and the third group (C, control), only completed the technical-tactical training. Each group increased their strength, except the control group. SC group had the best improvement in serve speed. L group increased the strength levels although there was no transfer from the improved strength to the hitting speed.